Winter spawning of Antarctic toothfish Dissostichus mawsoni in the Ross Sea region. Issue 5 (October 2019) - Parker, Steven J.; Stevens, Darren W.; Ghigliotti, Laura; La Mesa, Mario; Di Blasi, Davide; Vacchi, Marino
Abstract: A survey of Antarctic toothfish ( Dissostichus mawsoni ) was conducted in the northern Ross Sea region during the winter of 2016 to document the timing and location of spawning activity, to collect biological information about reproductive status during the spawning season and to look for temporal signals in biological data from D. mawsoni that may indicate a spawning migration of mature toothfish from the continental slope region to the northern Ross Sea region. The 58 day survey showed that spawning of D. mawsoni began on some seamounts by early July. No changes were detected between winter and summer in length, age, sex ratio or condition factor distributions for D. mawsoni in the northern Ross Sea as hypothesized following a spawning migration from the slope to the northern Ross Sea region. These results suggest that the distribution of D. mawsoni in the Ross Sea is mainly accomplished through ontogenetic migration and not annual return spawning migrations.